Antidepressants act by inducing autophagy controlled by sphingomyelin-ceramide - Gulbins, Anne; Schumacher, Fabian; Becker, Katrin Anne; Wilker, Barbara; Soddemann, Matthias; Boldrin, Francesco; Müller, Christian P.; Edwards, Michael J.; Goodman, Michael; Caldwell, Charles C.; Kleuser, Burkhard; Kornhuber, Johannes; et al. (Molecular Psychiatry, 2018)
Major depressive disorder (MDD) is a common and severe disease characterized by mood changes, somatic alterations, and often suicide. MDD is treated with antidepressants, but the molecular mechanism of their action is unknown. We found that widely used antidepressants such as amitriptyline and fluoxetine induce autophagy in hippocampal neurons via the slow accumulation of sphingomyelin in lysosomes and Golgi membranes and of ceramide in the endoplasmic reticulum (ER). ER ceramide stimulates phosphatase 2A and thereby the autophagy proteins Ulk, Beclin, Vps34/Phosphatidylinositol 3-kinase, p62, and Lc3B. Although treatment with amitriptyline or fluoxetine requires at least 12 days to achieve sphingomyelin accumulation and the subsequent biochemical and cellular changes, direct inhibition of sphingomyelin synthases with tricyclodecan-9-yl-xanthogenate (D609) results in rapid (within 3 days) accumulation of ceramide in the ER, activation of autophagy, and reversal of biochemical and behavioral signs of stress-induced MDD. Inhibition of Beclin blocks the antidepressive effects of amitriptyline and D609 and induces cellular and behavioral changes typical of MDD. These findings identify sphingolipid-controlled autophagy as an important target for antidepressive treatment methods and provide a rationale for the development of novel antidepressants that act within a few days.
EVALuna2:211626